Study of phase evolution and dielectric properties of Sr2Mn0.7Sn0.3O4 - Nirala G.; Upadhyay S. (My University, 2025)
Ruddlesden-Popper oxide Sr2Mn0.7Sn0.3O4 was synthesized by solid state method by calcining at different temperatures between 1200 and 1500 °C. The phase evolution during thermal treatments was investigated and it was shown that the powder calcined at 1500 °C and ceramics sintered at 1500 °C have single phase structure. Rietveld refinement of the XRD data confirmed tetragonal crystal structure having a = b = 3.9425 Å and c = 12.1230 Å lattice parameters and I4/mmm space group symmetry. Permittivity (ε), impedance (Z∗), dissipation factor (tan δ) and AC conductivity (σAC) of the samples were studied in the frequency range 1 kHz–2 MHz and temperature range 60–600 °C. An equivalent circuit comprising two parallel R-L elements and one constant phase element (CPE) model fitted the impedance data very well. Components of the equivalent circuit were correlated with compositional micro inhomogeneities in the sintered sample. Resonance-like feature observed in the dissipation factor at a particular temperature is attributed to the cancellation of capacitive and inductive reactants. Negative permittivity and loss of the sintered sample were compared with other ceramic oxides showing negative permittivity. © 2023 University of Novi Sad, Faculty of Technology. All rights reserved.